Quality of fetal heart rate monitoring with transabdominal fetal ECG during maternal movement in labor: A prospective study - Catarina Reis‐de‐Carvalho; Paulo Nogueira; Diogo Ayres‐de‐Campos (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Transabdominal electrocardiographic (TAfECG) acquisition of fetal heart rate (FHR) signals has recently been introduced into leading commercial cardiotocographic (CTG) monitors. Continuous wireless transmission of signals has raised the possibility of the technology being used during maternal mobilization in labor. This study aims to evaluate signal quality and accuracy of TAfECG acquisition of FHR signals during static and active maternal positions in labor when compared with Doppler signals and with the gold‐standard method of fetal scalp electrode (FSE). Material and Methods A total of 76 women with singleton term pregnancies in the active first stage of labor had simultaneously acquired FHR with TAfECG, Doppler, and FSE. Participants were asked to complete a supervised mobilization scheme, comprising five sequential 10‐min periods of lying down, standing, sitting, walking, and rocking on the birthing ball. The three FHR signals were compared, defining signal loss as the percentage of signals under 20 bpm or exceeding 250 bpm and accuracy as the difference with FSE values. Computer analysis was used to quantify variability, accelerations, and decelerations. Static labor positions (lying down, standing, and sitting) were compared with active labor positions (walking and rocking on the birthing ball). Results Average signal loss was 5.3% with TAfECG (3.2% in static and 7.4% in active positions) and 15.5% with Doppler (8.3% in static and 30.7% in active positions). Average accuracy was 3.5 bpm with TAfECG (1.9 bpm in static and 5.04 bpm in active positions) and 13.9 bpm with Doppler (3.2 bpm in static and 24.7 bpm in active positions). Average variability was similar with TAfECG and FSE in static positions but significantly higher with TAfECG in active positions (23.6 vs. 13.5 bpm, p < 0.001). Conclusions In static labor positions, TAfECG provides a low signal loss, similar to that obtained with FSE, and a good signal accuracy, so the technique can be considered reliable when the mother is lying down, standing, or sitting. During maternal movement, TAfECG causes an artificial increase in FHR variability, which can cause false reassurance regarding fetal oxygenation. Doppler signals are unreliable during maternal movements.